Considerations for Selecting Cognitive Endpoints and Psychological Patient-Reported Outcomes for Clinical Trials in Pediatric Patients With Sickle Cell Disease - Hood, Anna M.; Crosby, Lori E.; Stotesbury, Hanne; Kölbel, Melanie; Kirkham, Fenella J. (Frontiers in Neurology, 2022)
Pediatric patients with sickle cell disease (SCD) experience a range of medical complications that result in significant morbidity and mortality. Recent advances in prophylactic and curative treatment approaches have highlighted the need for sensitive and clinically-meaningful trial endpoints. The detrimental effects of cognitive and psychological difficulties on social and economic mobility are well described. Although numerous reviews have assessed cognitive outcomes in other rare genetic disorders, SCD has not received the same focus. This review describes the cognitive (i.e., executive function and processing speed) and psychological domains (i.e., depression and anxiety) that are consistently associated with SCD pathology and, therefore, may be of particular interest as clinical trial endpoints. We then discuss corresponding well-validated and reliable cognitive tests and patient-reported outcomes (PROs) that may be appropriate for clinical trials given their robust psychometric properties, ease of administration, and previous use in the SCD population. Further, we provide a discussion of potential pitfalls and considerations to guide endpoint selection. In line with the move toward patient-centered medicine, we identify specific tests (e.g., NIH Toolbox Cognition Module, Wechsler Cancellation Test) and psychological PROs (e.g., PROMIS depression and anxiety scales) that are sensitive to SCD morbidity and have the potential to capture changes that are clinically meaningful in the context of patients' day to day lives. In particularly vulnerable cognitive domains, such as executive function, we highlight the advantages of composite over single-test scores within the context of trials. We also identify general (i.e., practice effects, disease heterogeneity) and SCD-specific considerations (i.e., genotype, treatment course, and disease course, including degree of neurologic, pain, and sleep morbidity) for trial measures. Executive function composites hold particular promise as trial endpoints that are clinically meaningful, amenable to change, relatively easy to collect, and can be incorporated into the routine care of patients with SCD in various settings and countries.